Development of STEAM-Based Ethnomathematics Modules for Enhancing Students’ Problem-Solving Skills in Social Arithmetic - Auliya, Amara Sweetya; Hendikawati, Putriaji; Niyamae, Ade Noorliza (Jurnal Pendidikan MIPA, 2024)
Fostering problem-solving skills in social arithmetic is challenging as students often find the topic unengaging, hindering effective teaching and participation. This study aimed to design and develop STEAM and ethnomathematics-based e-module as a valid, practical, and effective learning resource for Grade VII junior high school students studying social arithmetic. By integrating the cultural context of Kudus culinary traditions, the e-module sought to enhance students' problem-solving abilities and engagement. The research utilized Hannafin and Peck’s development model combined with Tessmer’s formative evaluation approach, involving expert validation, individual trials, small group evaluations, and field testing. The findings revealed that the e-module was highly valid, with expert evaluations scoring it at 91.5%. Practicality assessments yielded scores of 98.3% for individual trials and 98.2% for small group evaluations, both categorized as "very practical." The module significantly improved learning outcomes, with an average score improvement of 43.6% and an N-Gain score of 71.6%, indicating its effectiveness. Moreover, the e-module enhanced students' problem-solving abilities by 41.8%. This study highlights the potential of integrating STEAM and ethnomathematics with cultural elements to create engaging learning materials, offering an innovative approach to improving students' mathematical understanding and problem-solving skills.      Keywords: etnomathematics, problem solving, STEAM. DOI: http://dx.doi.org/10.23960/jpmipa/v25i4.pp1738-1751